Cephalopod fauna in the Southern Ocean using the diet of wandering albatrosses Diomedea exulans:a stable isotopes approach - Guerreiro, Miguel Fernandes, 1989- (2012)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2012 The Southern Ocean is a key component in the climatic and ecological global system. Cephalopods play an important task in this ecosystem. However, they are difficult to collect and therefore the basic knowledge regarding their ecology is scarce. The wandering albatross, Diomedea exulans, is a cephalopod predator. Here I characterize the cephalopod component of D. exulans diet by collecting boluses and regurgitates of chicks from around the ocean, in South Georgia, Crozet and Kerguelen Islands. By using stable isotopes analyses of Nitrogen and Carbon on the squids found on the diet, I can determine the distribution and trophic level of them, an approach that may provide important information about the threats of D. exulans. D. exulans fed predominantly in Onychoteuthid and Histioteuthid squids and secondarily on cranchiids and giant squids. Kerguelen diet differs from the others due to the influence of these large bodied squids, further proving the idea that much of the diet of these seabirds comes from scavenging. Cephalopods of the Southern Ocean were distributed within three water masses (Subtropical, Subantarctic and Antarctic), except for South Georgia (Antarctic and Subantarctic). Much of the previous biogeographic distributions of these squids in the Indian sector were confirmed or expanded north, for the subantarctic region. Cephalopods on the Southern Ocean occupy a great trophic span, from Martialia hyadesi (3.52±0.25 TL) to Taningia danae (6.01±0.15 TL).Thus, squids play a key role in the trophic ecology of D. exulans, that feeds mainly of Antarctic and Subantarctic and secondarily of Subtropical squids. Based on these findings, we may argue that D. exulans have different threats within the Southern Ocean: in the Atlantic, Longliners operating in the nearby shelves are the main threat; In the Indian sector, there is different contributions from Subtropical Tuna fishing and longliners in the shelves, at ...